2020
DOI: 10.1007/s12144-020-00972-1
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal examination of nurses’ need satisfaction profiles: A latent transition analysis

Abstract: This study examined within-person and within-sample stability of need satisfaction profiles over a three-month period among a sample of 1319 nurses. This study also considered the implications of these profiles for employee functioning (vigor, need for recovery, and job satisfaction), as well as the role of perfectionism and job crafting in predicting profile membership. Results revealed four distinct need satisfaction profiles, which proved to have the same structure, and size, across measurement points. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 123 publications
(177 reference statements)
5
31
0
1
Order By: Relevance
“…Instead, target loadings and model-based coefficients of composite reliability (omega coefficient; o) are typically interpreted in a more holistic manner. However, prior research on psychological need states within the bifactor ESEM framework (e.g., Gillet et al, 2020;Huyghebaert-Zouaghi et al, 2020b;Sánchez-Oliva et al, 2017;Tóth-Kiraly et al, 2018) seems to suggest that G-factors may be considered welldefined when they present target loadings approximating or exceeding .400 and a coefficient of composite reliability near or above .600. S-factors tend to be weaker in bifactor representations than in first-order models (CFA or ESEM) because bifactor models rely on two factors to explain the covariance present at the item level for each specific item (Morin et al, 2016b).…”
Section: Analysesmentioning
confidence: 99%
See 4 more Smart Citations
“…Instead, target loadings and model-based coefficients of composite reliability (omega coefficient; o) are typically interpreted in a more holistic manner. However, prior research on psychological need states within the bifactor ESEM framework (e.g., Gillet et al, 2020;Huyghebaert-Zouaghi et al, 2020b;Sánchez-Oliva et al, 2017;Tóth-Kiraly et al, 2018) seems to suggest that G-factors may be considered welldefined when they present target loadings approximating or exceeding .400 and a coefficient of composite reliability near or above .600. S-factors tend to be weaker in bifactor representations than in first-order models (CFA or ESEM) because bifactor models rely on two factors to explain the covariance present at the item level for each specific item (Morin et al, 2016b).…”
Section: Analysesmentioning
confidence: 99%
“…Interestingly, recent research has shown that bifactor modeling and exploratory structural equation modeling (ESEM) allow to address two multidimensionality issues that may be present in multidimensional instruments designed to measure employees' psychological need states (e.g., Gillet et al, 2020;Huyghebaert-Zouaghi et al, 2020b;Sánchez-Oliva et al, 2017). These multidimensionality issues are ignored in more traditional CFA approaches (including Structural Equation Modeling).…”
Section: A Multidimensional Measurement Perspective On Psychological Need Statesmentioning
confidence: 99%
See 3 more Smart Citations